Smoking and presence of human papillomavirus correlates with lymphocyte density in the stroma of penile squamous cell carcinoma - Mumba, Chibamba; Mapulanga, Victor; Mwale, Nicholas K.; Ngalamika, Owen (Frontiers in Oncology, 2025)
BackgroundPenile squamous cell carcinoma (PSCC) is the most common malignancy of the penis. Considering the increase in incidence of PSCC in many countries, there is a need for better and effective therapies for these patients. The tumor microenvironment may offer insights into a better understanding of the tumor, which may inform on predictive and prognostic targets. In this study, we investigated immune cell infiltration into the stroma of PSCC, and how it may be affected by multiple factors including smoking, HIV infection, and/or HPV infection.MethodsWe carried out a prospective analytical cross-sectional study at the University Teaching Hospital in Lusaka, Zambia. Consenting patients with confirmed PSCC, attending the Urology Clinic and scheduled for partial or total penectomy were enrolled into the study. HIV testing by serology, HPV detection and genotyping on fresh tumors by real time PCR, hematoxylin and eosin (H&E) staining and immunohistochemistry staining for CD3+ and CD8+ cells on formalin-fixed paraffin-embedded tissue, and flow cytometry for immunophenotyping circulating immune cells were done.ResultsWe enrolled 33 participants into the study. The participants had a mean age of 56 years, the majority (84.8%) were HIV positive, high-risk HPV was detected in 63.6% of the tumors, and 57.6% were positive for both HIV and high-risk HPV. HPV-positive PSCC tumors had a significantly lower proportion of infiltrating lymphocytes in the stroma on H&E staining than HPV-negative tumors [18% vs 53%; p=0.025]. Smokers had a significantly lower number of infiltrating CD8+ cells in the stroma than non-smokers [68 vs 99; p=0.035]. No difference in the density of stromal lymphocytes between HPV/HIV co-infected and non-co-infected individuals was observed. There was a statistically significant positive correlation in number of CD3+ (⍴=0.38; p=0.027) and CD8+ (⍴=0.40; p=0.02) cells in the stroma and intra-tumor. Factors including histological stage, tumor grade, HPV status, and HIV status seem to influence the correlation in number of stroma and intra-tumoral immune cells.ConclusionSmoking and presence of hrHPV is associated with a lower density of infiltrating lymphocytes in the stroma of PSCC. There is a positive correlation in the number of CD3+ and CD8+ cells between the stroma and intra-tumoral compartment of PSCC.